Study of Pre-disposing Factors of Acute Exacerbation of Chronic Obstructive Pulmonary Disease and Antibiotic Prescribing Pattern with Reference to Antibiotic Sensitivity Test - Shrestha, R.; Shrestha, B.; Shakya Shrestha, S.; Pant, A.; Prajapati, B.; Karmacharya, B.M. (Kathmandu University Medical Journal, 2017)
Background Chronic Obstructive Pulmonary Disease (COPD) affects about 329 million people worldwide, which is nearly 5% of the entire global population. In the context of Nepal, COPD accounts for 43% of the non-communicable disease burden and 2.56% of hospitalizations. Various pre-disposing factors like bacterial, viral, fungal, smoking, occupational exposures and genetic factors have been proposed to precipitate COPD and its exacerbation though, the definitive pre-disposing factors and factors related to acute exacerbation have not been determined in the context of Nepal.Objective To find out the pre-disposing factors and the related causative agents for COPD.Method A cross sectional study was conducted in a tertiary care hospital. Patients of all age group who were diagnosed as COPD and admitted in the hospital were included in this study. Patients were interviewed using structured questionnaire. The socio-demographic data including personal and medical history were recorded from those participants. In addition, sputum from those patients was sent for culture to investigate the possible responsible pathogens as well as its antibiotic sensitivity pattern.Result A total of 150 patients having Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) who have admitted from either emergency or out-patient department of the hospital were included in this study. Among the total number of patients, more than half of them were female (n=82). In addition, analysis of occupations shows that most of them were either farmer (36.0%) or housewife (30.7%). In total studied patients (n=150), most of them were using traditional firewood (83%) for cooking purpose and majority of patients (91%) were smokers. Most of the sputum samples show growth of gram-positive cocci (26.7%) and gram negative bacilli (27.5%). Considering the overall sensitivity pattern, the higher sensitivity was recorded for Co-trimoxazole and Ciprofloxacin while higher rate of resistance was noted for Penicillin group of drugs. The most widely used antibiotics were found to be Cephalosporin group of drugs (68%).Conclusion The present study revealed that the case of COPD is more in female and the commonest pre-disposing factor is found to be smoke/firewood. Cephalosporin group of drugs is the most commonly prescribed drug.